Penerapan Model Pembelajaran Problem Based Learning dengan Menggunakan Media Wordwall untuk Meningkatkan Keaktifan Siswa SD pada Pelajaran Bahasa Indonesia - Pramesti, Ardian Agustin; Ekowati, Dyah Worowirastri; Febriyanti, Fitria (Universitas Nusantara PGRI Kediri, 2023)
Learning Indonesian in elementary schools often encounters several obstacles, one of which is the activeness of students in participating in learning. These conditions can affect student learning outcomes in these subjects. The purpose of this study is to increase the activity of students in learning Indonesian by using wordwall media and applying the PBL learning model. This study used a class action research method with 28 IC class students as subjects at SDN Purwantoro 1 Malang City. This research was conducted in two cycles with each cycle consisting of planning, action, observation and reflection. The results showed that the application of the PBL learning model with Wordwall media at SDN Purwantoro 1 Malang class 1C could increase the activeness of students in learning Indonesian. In the pre-cycle activities, the activeness of the students was only 50%, while in the first cycle it increased to 62.85%. Whereas in cycle II the activity greatly increased to 86.42%. It can be concluded that the application of the PBL learning model with Wordwall media can increase student activity in learning Indonesian in elementary school.